Introduction to the famous sufism in the subcontinent: برصغیر میں موجود تصوف کے مشہور سلسلوں کا تعارف - Ahmad, Dr. Mehmood; Ullah, Dr. Muhammad Zia; Bibi, Shazia (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
There are at least 200 slasals mentioned in the subcontinent, but the famous slasals of the subcontinents are four. All the rest are their same branches. They worked day and night for the spiritual improvement of man. His teachings teach human well-being everywhere. He taught man how to live by which we can prosper.